Spinal Schwannoma as Pregnancy Related Spinal Tumor - Kadek Dede Frisky Wiyanjana; Kevin Kristian Putra; Sri Maliawan; I Made Gotra (Indoscholar, 2020)
Spinal schwannoma is the most common benign spinal tumors that originated from peripheral nerve sheath tumors. Male and females are equally affected. Due to hormonal imbalance during pregnancy, it might affect the release of the tumor-growth factor. The symptoms usually start with pain and sensory loss at the spinal cord level. We report a case of thoracolumbar schwannoma with a history of chronic low back pain since post-pregnancy. A Thirty-Seven years old female, suffered chronic low back pain for 3 years since she had a pregnancy. In the last 4 months, she suffered paresis and tingling sensation on the right foot. MRI shown intradural mass at Th 12 – L2. Biopsy, tumor resection, and laminectomy were performed to do the histopathology analysis, resect, and stabilization. Histopathology examination revealed Schwannoma types. The patient was discharged three days after complete tumor resection and stabilization, with an improvement of neurological function. Spinal Schwannoma can occur as a Pregnancy-related spinal tumor (PRST), it can be diagnosed during pregnancy or within a year after delivery. The incidence is rare, therefore proper workup and early examination are needed and followed by careful and considerate treatment.